In vivo electron paramagnetic resonance imaging of differential tumor targeting using cis‐3, 4‐di(acetoxymethoxycarbonyl)‐2, 2, 5, 5‐tetramethyl‐1‐pyrrolidinyloxyl. Issue 4 (14th June 2013) - Redler, Gage; Barth, Eugene D.; Bauer, Kenneth S.; Kao, Joseph P.Y.; Rosen, Gerald M.; Halpern, Howard J.
<x xml:space="preserve">Abstract</x> Purpose Electron paramagnetic resonance spectroscopy promises quantitative images of important physiologic markers of animal tumors and normal tissues, such as pO2, pH, and thiol redox status. These parameters of tissue function are conveniently reported by tailored nitroxides. For defining tumor physiology, it is vital that nitroxides are selectively localized in tumors relative to normal tissue. Furthermore, these paramagnetic species should be specifically taken up by cells of the tumor, thereby reporting on both the site of tumor formation and the physiological status of the tissue. This study investigates the tumor localization of the novel nitroxide, cis‐3, 4‐di(acetoxymethoxycarbonyl)‐2, 2, 5, 5‐tetramethyl‐1‐pyrrolidin‐yloxyl 3 relative to the corresponding di‐acid 4. Methods We obtained images of nitroxide 3 infused intravenously into C3H mice bearing 0.5‐cm3 FSa fibrosarcoma on the leg, and compared these with images of similar tumors infused with nitroxide 4. Results The ratio of spectral intensity from within the tumor‐bearing region to that of normal tissue was higher in the mice injected with 3 relative to 4. Conclusion This establishes the possibility of tumor imaging with a nitroxide with intracellular distribution and provides the basis for EPR images of animal models to investigate the relationship between crucial aspects of tumor microenvironment and malignancy and its response to therapy. Magn Reson Med 71:1650–1656, 2014. © 2013 Wiley Periodicals, Inc.